Coding of Barrett's oesophagus with high-grade dysplasia in national administrative databases: a population-based cohort study. Issue 6 (9th June 2017) - Chadwick, Georgina; Varagunam, Mira; Brand, Christian; Riley, Stuart A; Maynard, Nick; Crosby, Tom; Michalowski, Julie; Cromwell, David A
Abstract : Objectives: The International Classification of Diseases 10th Revision (ICD-10) system used in the English hospital administrative database (Hospital Episode Statistics (HES)) does not contain a specific code for oesophageal high-grade dysplasia (HGD). The aim of this paper was to examine how patients with HGD were coded in HES and whether it was done consistently. Setting: National population-based cohort study of patients with newly diagnosed with HGD in England. The study used data collected prospectively as part of the National Oesophago-Gastric Cancer Audit (NOGCA). These records were linked to HES to investigate the pattern of ICD-10 codes recorded for these patients at the time of diagnosis. Participants: All patients with a new diagnosis of HGD between 1 April 2013 and 31 March 2014 in England, who had data submitted to the NOGCA. Outcomes measured: The main outcome assessed was the pattern of primary and secondary ICD-10 diagnostic codes recorded in the HES records at endoscopy at the time of diagnosis of HGD. Results: Among 452 patients with a new diagnosis of HGD between 1 April 2013 and 31 March 2014, Barrett's oesophagus was the only condition coded in 200 (44.2%) HES records. Records for 59 patients (13.1%) contained no oesophageal conditions. The remaining 193 patients had various diagnostic codes recorded, 93 included a diagnosis of Barrett's oesophagus and 57 included a diagnosis of oesophageal/gastric cardia cancer. Conclusions: HES is not suitable to support national studies looking at the management of HGD. This is one reason for the UK to adopt an extended ICD system (akin to ICD-10-CM).